Hydrogen generation during hydrothermal alteration of peralkaline granite. (1st September 2021) - Truche, Laurent; Bourdelle, Franck; Salvi, Stefano; Lefeuvre, Nicolas; Zug, Apolline; Lloret, Emily
Abstract: It is well known that oxidation of ferrous to ferric iron by water can generate molecular hydrogen (H2 ), with the most widely recognized natural manifestation being serpentinization of olivine and pyroxene in ultramafic rocks. A less known yet extremely important source of natural H2 are peralkaline igneous intrusions, where spectacular enrichments of H2 are documented from fluid inclusions and as free gas migrating through fractured rocks and soils. Of these occurrences, the best studied are those at Strange Lake in Canada, Lovozero and Khibiny in Russia, and Ilímaussaq in Greenland. Based on petrographic observations and fluid inclusions analysis, it has been proposed that the hydrothermal alteration of arfvedsonite, an Fe II -bearing amphibole, is the source of H2 in this context, although it is yet to be unequivocally demonstrated. To investigate the generation of H2 during alteration of peralkaline granites, we performed hydrothermal experiments on pure arfvedsonite grains and arfvedsonite-bearing granite (10 wt% arfvedsonite) from the Strange Lake pluton (Canada). These materials, in the presence of aqueous solutions, were sealed inside gold capsules or placed within titanium autoclaves, which allowed monitoring H2 generation in function of temperature (280–400 °C), chlorinity (0 and 3 m NaCl), pH, and starting mineral assemblage. Blank experiments were conducted to quantify the background amounts of H2 generated from Au/Ti oxidation, diffusing through the reaction cells, release from fluid inclusions or otherwise occluded in minerals. Solids were characterized by XRD, SEM, TEM on FIB foils, and STXM-XANES. Outcomes of this study demonstrate the production of H2 in agpaitic peralkaline rocks by the hydrothermal alteration of arfvedsonite. The rate of H2 production, normalized to the specific surface area of arfvedsonite, increases with temperature from 1100 to 2200 pmol cm −2 day −1 between 280 and 400 °C, respectively. Chlorinity tends to have a negative impact on the reaction rate, while circumneutral to alkaline conditions clearly promote H2 generation. Altering whole granite samples instead of arfvedsonite grains only also enhances H2 production rate. The presence of aluminum, released from microcline and albite dissolution, may increase both the solubility and the dissolution rate of arfvedsonite by promoting precipitation of phyllosilicates. At least two different types of phyllosilicates were observed, chlorite and smectite. Magnetite and secondary zircon were also identified at the surface of reacted arfvedsonite (Zr content = 1200 ppm). The H2 production rates reported here at 280–400 °C are comparable, and even faster than those documented for serpentinization of olivine and harzburgite. A major feature of arfvedsonite alteration in peralkaline plutons is the formation of aegirine as a replacing mineral. However, aegirine was never observed in the reacted solids from our experiments, under the condition tested (up to 400 °C and 400 bar). This may be an effect of pressure, oxygen fugacity, or reaction progress, parameters that remain to be investigated to better constrain the reaction mechanism of arfvedsonite alteration. Agpaitic peralkaline igneous intrusions thus represent a fertile geological setting for deep microbial subsurface ecosystems, abiotic synthesis of organic molecules, and natural H2 exploration for an alternative source of energy.